MANAJEMEN KEUANGAN KELUARGA PEDAGANG DI PASAR SIBANG GEDE - Pramudya, I Made Krisna Maha; Arisena, Gede Mekse Korri (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2024)
The income of traders depends on uncertain sales income every day. To be able to manage family finances, management, and planning are needed to ensure that expenses are not greater than income. This study aims to examine the understanding of financial management, the application of financial management, and the obstacles to financial management for traders in the Sibang Gede market. This study's data and information collection methods included interviews using questionnaires and documentation. The analysis method used is qualitative descriptive analysis. The results of this study indicate that traders in the Sibang Gede market do not understand financial management. Traders choose to record income daily, do not apply long-term planning, apply short-term planning, and own assets in the form of houses and motorbikes. Traders in the Sibang Gede market do not make financial plans, do not record family finances in books, and do not compile budgets. Traders do not have investments, and all traders in the Sibang Gede market choose to use banks as a place to save. The obstacles Sibang Gede market traders face are income instability caused by fluctuations in consumer demand, traders not being accustomed to making financial reports, and traders not being familiar with modern finance.